First instar larva of Atractocerus brasiliensis (Lepeletier & Audinet-Serville, 1825) (Lymexylidae, Atractocerinae) - Sônia A. Casari; Fabiano F. Albertoni (Papéis Avulsos de Zoologia, 2013)
The first instar larva of Atractocerus brasiliensis (Lepetelier & Audinet-Serville, 1825) from state of Goiás, Brazil, and reared in laboratory, is described and illustrated. This is the second species with known first instar larva for the genus and the third for the family. Comparisons with mature larva of this species and with the other known first instar larvae are presented. Illustrations of first instar and mature larvae are also included.